Технико-экономические показатели геотермальных циркуляционных систем теплоснабжения с горизонтальными и вертикальными скважинами - Редько, А. А.; Бугай, В. С. (НТУ "ХПИ", 2009)
In this article technical and economic indicators of geothermal circulating systems (GCS) heat supplies with vertical and horizontal wells, their comparison. Considered GCS with horizontal well allows to improve technical and economic indicators compared with GCS with vertical well.
Keywords: теплоснабжение; геотермальные воды; теплоэнергия; горизонтальная скважина; вертикальная скважина; бурение; гидродинамика; теплоноситель